Enhancement of fire-fighting efficiency of water mist systems with hydraulic water spray method by the intake of surface active agent additives into the fire-fighting liquid - Petukhovskiy Сергей Геннадьевич; Zanevskaya Ю. В.; Navrotskiy Олег Дмитриевич; Emel’yanov В. К. (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
The research work was carried out to determine dependences of the size of drops of fire fighting composition was sprayed by hydraulic way under the injection pressure of 0.6 MPa on additives of fluorid and hydrocarbon surface active agents. It was determined that to decrease the size of drops of jet, which is created by water spray fire extinguishment means with hydraulic sprayers under the pressure of the fire-fighting liquid into the sprayer of 0.6 MPa, it may be recommended to apply fire-fighting composition, representing a 0,02 % water solution of triethanolamine laurylsulfate.